The Characteristic of the Gastric Secretion After Gastric Cryodenervation and Cryopreserved Placenta Extract Administration - Koshurba, Illia; Hladkykh, Fedir; Chyzh, Mykola; Marchenko, Mykhailo; Belochkina, Iryna (Innovative Biosystems and Bioengineering, 2023)
Background. Peptic ulcer is a prevalent gastrointestinal tract disease worldwide. One of the treatment methods for the indicated pathology is trunk gastric cryodenervation (TGC), the feature of which is the preservation of the regenerative potential of n. vagus. Cryopreserved placenta extract (CPE) caught our attention among modern means capable of stimulating regeneration processes. Objective. We are aimed to characterize the state of gastric secretion after TGC and the application of СPE. Methods. TGC was performed by cryoinfusion on the front and back trunks of the abdominal part of n. vagus. Gastric secretion was studied using the H.A. Shay method. Results. On the 30th day after TGC, a statistically significant (p < 0.001) decrease in the total acidity of gastric juice by 33.7% and a decrease (p < 0.01) in the level of free acidity were observed compared to intact animals. Administration of СPE after TGC resulted in a statistically significant (p < 0.001) decrease in total acidity by 24.2 % and a statistically significant (p < 0.001) decrease in free acidity by 48.7% compared to the parameters of intact rats. This led to a statistically significant (p < 0.001) decrease in the "free/bound acidity" ratio compared to the indicator of intact animals (1.4 ± 0.03 RU) which was higher than the similar ratio observed after esomeprazole usage or TGC. Conclusions. Administration of СPE contributed to the partial regeneration of n. vagus, as indicated by an increase in the level of total acidity to 104.1 ± 4.7 RU and a statistically significant (p < 0.001) decrease in the "free/bound acidity" ratio compared to the indicator of intact animals.